2017
DOI: 10.1007/s40258-016-0301-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Insulin Degludec Plus Liraglutide (IDegLira) in a Fixed Combination for Uncontrolled Type 2 Diabetes Mellitus in Sweden

Abstract: BackgroundPatients with uncontrolled type 2 diabetes mellitus (T2DM) are a priority group for intensified therapy without weight gain and with low risk of hypoglycaemia.ObjectiveThis study evaluates the cost effectiveness of insulin degludec plus liraglutide (IDegLira, Xultophy®) compared with six potential intensification treatment options for patients with T2DM that is uncontrolled with basal insulin.MethodsThe Swedish Institute for Health Economics (IHE) Cohort Model of Type 2 Diabetes was used with Swedish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…These findings are consistent with other published health economic analyses of IDegLira. Cost‐effectiveness evaluations based on clinical trial data on IDegLira have shown that it is likely to improve clinical outcomes and be cost‐effective versus several comparator regimens (basal insulin, basal‐bolus insulin, and GLP‐1 receptor agonists in combination with insulin) in patients with type 2 diabetes in the United States, the Netherlands, the Czech Republic, Sweden, the United Kingdom and Spain . Comparable health economic outcomes from the present study based on real‐world evidence are reassuring, as they indicate that the benefits of IDegLira observed in RCTs translate to the real‐world setting, and that similar improvements in long‐term outcomes with IDegLira can be anticipated for patients in routine clinical practice.…”
Section: Discussionsupporting
confidence: 55%
“…These findings are consistent with other published health economic analyses of IDegLira. Cost‐effectiveness evaluations based on clinical trial data on IDegLira have shown that it is likely to improve clinical outcomes and be cost‐effective versus several comparator regimens (basal insulin, basal‐bolus insulin, and GLP‐1 receptor agonists in combination with insulin) in patients with type 2 diabetes in the United States, the Netherlands, the Czech Republic, Sweden, the United Kingdom and Spain . Comparable health economic outcomes from the present study based on real‐world evidence are reassuring, as they indicate that the benefits of IDegLira observed in RCTs translate to the real‐world setting, and that similar improvements in long‐term outcomes with IDegLira can be anticipated for patients in routine clinical practice.…”
Section: Discussionsupporting
confidence: 55%
“…The validation indicated that the model has a predictive accuracy in line with other models of T2D. This model is applicable to CEAs of diabetes in Sweden as it is based on Swedish risks, healthcare system, and costs [27][28][29] .…”
Section: Paɵents Inadequately Controlled On Meƞormin Paɵents Inadequamentioning
confidence: 56%
“…These CEAs were conducted using the IHE Diabetes Cohort Model 26 , which has been used in other CEAs in Sweden [27][28][29] . Briefly, this model uses cohort simulation to estimate the cost-effectiveness of competing interventions for T2D.…”
Section: Methodsmentioning
confidence: 99%
“…These improvements may provide substantial cost savings for healthcare payers through reduced expenditure on the treatment of diabetesrelated complications 33 . Evidence from available cost-effectiveness analyses further support the role of HbA 1c and BMI in determining long-term outcomes; improvements in which have been shown to offset higher initial treatment costs 34,35 . The estimated relative treatment effects for IDegLira vs iGlarLixi, derived from this indirect treatment comparison, could be used as a basis for future cost-effectiveness analyses.…”
Section: Discussionmentioning
confidence: 96%